Academic library: The problem of performance evaluation - Rudžionienė, Jurgita (Information & Media, 1997)
The aim of this article is to discuss the core factors of academic library performance evaluation. An academic library as a part of an academic institution must prove its existence and demonstrate a quality of services supporting the teaching and research processes of the high school. The decentralization of responsibility has been an important innovation in the management of universities, as in all institutions. As a consequence of the decentralization of economic responsibility, the government’s interest in the "value of money" allocated to libraries has increased. Focusing on business enterprise experience, the classical opinion of a library as a collection of books is changing to one involving more of a service orientation. Much attention is currently being devoted to the process of developing library-performance indicators for the evaluation of academic library performance.